Penile nerve block at the base of penis in combination with intravenous ketamin plus midazolam versus general anaesthesia(GA) in children undergoing circumcision for post operative pain management in the Eastern Nepal - Sharma, NR; Timalsena, P; Rai, U (Journal of Chitwan Medical College, 2014)
Adequate post operative analgesia in children provides satisfactory psychological objective of this study was to compare the post operative analgesia requirement and child satisfaction between two groups, general anaesthesia(GA) alone and GA in combination with penile nerve block. This prospective randomized study was conducted in 50 children aged 6 to 14 years, who underwent circumcision. The boys were randomly allocated into two groups. Group A (n = 25) received GA with Single shot ketamin 2mg/kg IV plus midazolam 0.1 mg/kg and dorsal penile nerve block at the base of penis prior to circumcision with and Group B (n = 25) received GA with ketamine 2mg/kg IV plus midazolam 0.1 mg/kg plus halothane by laryngeal mask. Severity of pain was assessed quantitatively by children’s hospital eastern Ontario pain scale (CHEOPS). The pain intensity was assessed at one hour A1 in group A and B1 for group B and at two hour A2 for group A and B2 for group B during postoperatively period for two hours. Statistical analysis was done by SPSS method. The post operative analgesia was satisfactory with CHEOPS score 6 or <6 in group A 1. In group A 2 twenty two out of twenty five cases had CHEOPS score <6.Where as in group B1 and B2 it was > 6 .Which was statistically 100% significant. In conclusion, combined penile nerve block in combination with intravenous ketamine plus midazolam is the satisfactory method of Post operative pain management in children undergoing circumcision. DOI: http://dx.doi.org/10.3126/jcmc.v4i1.10846 Journal of Chitwan Medical College 2014; 4(1): 33-36